1996
DOI: 10.1074/jbc.271.30.17798
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 5′-AMP-activated Protein Kinase Activity by the Noncatalytic β and γ Subunits

Abstract: The mammalian 5-AMP-activated protein kinase is a heterotrimer consisting of an ␣ catalytic subunit and ␤ and ␥ noncatalytic subunits, each of which is represented in a larger isoprotein family, related to the SNF1 kinase and its interacting proteins in yeast. In this study, we have used mammalian cell transfection to compare the activities of the two ␣ subunit isoforms, ␣-1 and ␣-2, and to study the influence of the noncatalytic subunits on enzyme subunit association and activity. Expression of epitope-tagged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
172
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(179 citation statements)
references
References 28 publications
7
172
0
Order By: Relevance
“…Maximum activity requires all three subunits (3). The catalytic AMPK ␣1-(1-312) fragment is constitutively active whereas the ␣1-(1-392) fragment is autoinhibited, and neither bind ␤␥ subunits (2).…”
mentioning
confidence: 99%
“…Maximum activity requires all three subunits (3). The catalytic AMPK ␣1-(1-312) fragment is constitutively active whereas the ␣1-(1-392) fragment is autoinhibited, and neither bind ␤␥ subunits (2).…”
mentioning
confidence: 99%
“…In mammals, the formation of the heterotrimer is necessary for AMPKa activity (Dyck et al, 1996;Woods et al, 1996). In yeast, SNF4 (the g-subunit) deletion or simultaneous deletions of the three b-subunits totally inactivates the SNF1 activity in vivo (Carlson et al, 1981;Schmidt and McCartney, 2000), indicating that they all play important roles within the complex.…”
mentioning
confidence: 99%
“…A constitutively active AMPK mutant containing only the a-subunit kinase domain, CcaAMPK, provided an alternative, but the kinase domain alone possesses weak kinase activity in mammalian cells, and maximum AMPK activity requires all three subunits. 6,14 We therefore constructed a replication-defective adenovirus expressing NcaAMPK, which has higher kinase activity and suppresses anoxia-induced apoptotic cell death more efficiently than CcaAMPK. Although higher dose, 100 MOI, CcaAMPK transduction in the cells increased SAMS peptide phosphorylation rate by B35% compared with 50 MOI, the dose we used in this study, we did not find more potent inhibition of cell death in CcaAMPK-overexpressing cells with 100 MOI (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Several kinds of constitutively active AMPK mutants have been investigated, including AMPKa1 (amino acids (aa) 1-312, Thr172-Asp: T172D), 14,15 AMPKg2 (Arg302-Gln), 16 and AMPKg1 (His150-Arg). 17 Although it has been reported that maximum activity of AMPK requires all three subunits, 6 AMPKa1 (1-312, T172D) lacks both the binding domain for interactions with the b-subunit and the autoinhibitory domain, which inhibits the self-kinase activity. 14 The b-subunit plays a role in modulating subcellular localization through its phosphorylation and myristoylation, 18,19 so that the ability to bind the b-subunit might be critical for the catalytic a-subunit to select its appropriate substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation